SPECIFIC FEATURES OF LYRICAL POETRY (BASED ON THE MATERIAL OF RUSSIAN POETRY OF THE 2ND HALF OF THE XX CENTURY) (Scientific journal of the Fergana State University, 2023)
The article examines the specific features of lyrical poetry of the second half of the 20th century, which is characterized by complex syntax and species diversity.Among the most important features of the lyrics of this period should be noted the appeal to a large number of poetic and non-poetic forms, the desire to discover more and more new forms for poetry and to adapt traditional ones. In the formation of these various genres, the possibilities of interaction between the poet and language, the poet and artistic reality, the specific features of the development of the poetic system as a whole are especially clearly visible.